2016
DOI: 10.1080/15384047.2016.1252880
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21 is a novel regulator of Par-4 in colon and pancreatic cancer cells

Abstract: The prostate apoptosis response protein 4 (Par-4) is a tumor-suppressor that has been shown to induce cancer-cell selective apoptosis in a variety of cancers. The regulation of Par-4 expression and activity is a relatively understudied area, and identifying novel regulators of Par-4 may serve as novel therapeutic targets. To identify novel regulators of Par-4, a co-immunoprecipitation was performed in colon cancer cells, and co-precipitated proteins were identified by mass-spectometry. TRIM21 was identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…S100A10, a small dimeric helix-loop-helix protein residing in a tight complex with Annexin A2, appeared to regulate the intracellular trafficking of a variety of membrane-resident proteins, such as cathepsin B (38). TRIM21 is an E3 ubiquitin ligase associated with autoimmune diseases (39), and the dysregulation of TRIM21 facilitates human cancer development (40,41). This study detected a significant decrease of TRIM21 and Annexin A2 levels in PGCCs with their daughter cells after S100A4 knockdown as well as a reduced nuclear translocation of S100A10 in daughter cells, while 14-3-3 ζ/δ and Ezrin did not vary.…”
Section: Discussionmentioning
confidence: 99%
“…S100A10, a small dimeric helix-loop-helix protein residing in a tight complex with Annexin A2, appeared to regulate the intracellular trafficking of a variety of membrane-resident proteins, such as cathepsin B (38). TRIM21 is an E3 ubiquitin ligase associated with autoimmune diseases (39), and the dysregulation of TRIM21 facilitates human cancer development (40,41). This study detected a significant decrease of TRIM21 and Annexin A2 levels in PGCCs with their daughter cells after S100A4 knockdown as well as a reduced nuclear translocation of S100A10 in daughter cells, while 14-3-3 ζ/δ and Ezrin did not vary.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The literature reports that decreased expression of TRIM21 predicts shorter survival times in patients with hepatocellular carcinoma and diffuse large B-cell lymphoma 8 , 9 but better prognosis in patients with pancreatic cancer. 11 TRIM21 has also been identified as a diagnostic biomarker for breast cancer. 23 In our study, TRIM21 was noticeably downregulated in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 10 TRIM21 confers drug resistance to cisplatin to colon cancer cells via the suppression of Par-4. 11 In breast cancer, TRIM21 was found to be capable of downregulating the expression of Sal-like 4 (SALL4) and Lifeguard. 12 , 13 However, the clinical significance of TRIM21 and its role in cell proliferation in breast cancer remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus (SLE), and Sjogren's syndrome (39). Recent studies have suggested that TRIM21 may play an essential role in the tumor suppressor or drug-induced apoptosis of cancer cells (41,42). However, contradictory results, that TRIM21 may target IRF3 after RNA viral infection, have been reported (43,44).…”
mentioning
confidence: 99%